The Influence of Brand Image, Switching Barrier, and Perceived Quality on Customer Loyalty of Telkomsel Users in Sidoarjo - Maulana, Farid Raditya; Febriansah, Rizky Eka; Prapanca, Detak (Journal of Economics Education and Entrepreneurship, 2025)
This study aims to analyze the effect of brand image, switching barriers, and perceived quality on customer loyalty among Telkomsel users in Sidoarjo. This study employs a quantitative approach involving 100 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using SPSS 26. Various statistical tests were conducted, including validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, coefficient of determination (R²) test, and partial test (t-test). The results indicate that the three independent variables have a significant effect on customer loyalty. Switching barriers play the most crucial role as they prevent customers from changing providers. Perceived quality, particularly in terms of network reliability and service excellence, strengthens customer commitment. Meanwhile, brand image serves as a key factor in shaping customer perceptions but has a relatively lower impact. This study concludes that an integrated strategic approach is necessary to enhance customer loyalty, including reinforcing switching barriers, improving perceived quality, and maintaining a strong brand image. These findings offer insights for telecommunications companies to remain competitive in a dynamic market.